Pendidikan Anti Korupsi dalam Perspektif Islam - Dias Raisya Nur Azizah; Iqbal Amar Muzaki; Afiyatun Kholifah (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
Corruption has become a disease that is difficult to cure, except for the desire to repent by the perpetrators of corruption and the growing desire to be honest and fair from each individual, especially to teach students, both students and college students. The purpose of anti-corruption education in an Islamic perspective is to make students as individuals who have faith, piety, and noble character. So that the younger generation can prioritize piety and fear of Allah Ta'ala, as well as prioritizing the interests of the people/society and not only prioritizing their own interests or pleasures that can cause harm to society. The method of implementation in this scientific article uses the literature review method and uses an empirical historical approach, which is an approach that looks at each problem discussed in the social reality that actually occurs.  Anti-corruption education is a way for the state to be able to instill anti-corruption values to students. And anti-corruption education from an Islamic perspective can help instill moral values based on religion.